2004
DOI: 10.1002/ijc.20030
|View full text |Cite
|
Sign up to set email alerts
|

Increasing colorectal cancer incidence rates in Japan

Abstract: We examined trends of colorectal cancer incidence rates among Japanese (Miyagi Prefecture) and United States (US) whites (State of Connecticut) between 1959 and 1992. Agestandardized rates in Japan have increased dramatically and are now similar to US white rates. For both colon and rectum, age-specific rates in Japanese men born after 1930 exceed those in US whites, and the Japanese excess increases with year of birth. Similar patterns are evident for women. The current trends suggest that colorectal cancer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
106
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(110 citation statements)
references
References 9 publications
1
106
1
2
Order By: Relevance
“…For Japanese men born around 1930, values were comparable to-or even higher than-those of Connecticut white men. 1 Colorectal cancer incidence, however, is not only due to changes in underlying rates of the disease, but is also influenced by advancements in screening and early diagnosis. [2][3][4] National mortality rates are less influenced by any such modification and provide therefore less biased information on longterm trends.…”
Section: Dear Sirmentioning
confidence: 99%
“…For Japanese men born around 1930, values were comparable to-or even higher than-those of Connecticut white men. 1 Colorectal cancer incidence, however, is not only due to changes in underlying rates of the disease, but is also influenced by advancements in screening and early diagnosis. [2][3][4] National mortality rates are less influenced by any such modification and provide therefore less biased information on longterm trends.…”
Section: Dear Sirmentioning
confidence: 99%
“…It has been considered to be less common among Asians and Caucasians [6,7] . However, recent studies have shown an increasing trend in these populations [8][9][10] . Variation in the incidence of colorectal neoplasia has been observed in populations and even in cities of one country.…”
Section: Introductionmentioning
confidence: 98%
“…Hoy en día, se ha determinado que el CCR es una enfermedad heterogénea y surge por la acumulación secuencial de procesos genéticos y epigenéticos 6,7 . Se ha descrito que el CCR esporádico se desarrolla principalmente por 3 eventos moleculares carcinogénicos: la inestabilidad cromosómica (CIN), la inestabilidad microsatelital (MSI) y el fenotipo metilador (CIMP) 8 .…”
unclassified